Pathologic light chain amyloidosis oligomer detection in urinary extracellular vesicles as a diagnostic tool for response and progression of disease - Cooper, Shawna A.; Dick, Christopher J.; Misra, Pinaki; Leung, Nelson; Schinstock, Carrie A.; Ramirez-Alvarado, Marina (Frontiers in Oncology, 2022)
Light Chain (AL) Amyloidosis is a plasma cell dyscrasia producing amyloidogenic light chains (LC) that misfold and form amyloid deposits that cause damage in vital organs, primarily the heart and kidneys. Urinary extracellular vesicles (uEVs) are nanoparticles produced by renal epithelial cells throughout the nephron. We previously showed that uEVs from active renal AL amyloidosis patients contain LC oligomers that are large (>250kDa), resistant to heat and chemical denaturation, but of low abundance. Renal dysfunction in AL amyloidosis results in high urine protein, compounding technical challenges to use uEVs as analytical tools. In this study, we assess the use of uEVs as analytical diagnostic tools for response and disease progression in AL amyloidosis. Our results suggest that uEV protein concentration, urine volume, and particle concentrations are not directly correlated. Multiple strategies for overcoming non-specific antibody binding in uEV samples were validated in our study. We demonstrated that the sensitivity for pre-clinical testing is improved with a urine sample requirement algorithm that we developed. The findings of our study will provide a pathway toward development of critically needed tools for patient management. Sensitive detection of LC oligomers from a non-invasive urine sample rather than an invasive renal biopsy will reduce patient burden and healthcare costs. The ability to detect LC oligomers in patients with renal progression, despite positive hematologic response; will allow clinicians to confidently treat, but not overtreat, patients at risk of ongoing significant renal injury.